Effects of Pretreatments on the Storage Characteristics of Fresh and Dried Guava (Psidium Guajava L) - Khin, Ma Ma Kyi (1991)
The studies on guava (var.Vietnamese) precooled at 0 hr(immediately) and 4 hr after harvest,and stored at 5°C and 10°C were carried out. Guava stored at 10°C was able to undergo a ripening process. Chilling injury was observed at sec storage. Precooling did not seem to have any beneficial effect on guava.The characteristics considered were weight loss , colour change of skin, hardness, soluble solids content, pH, titratable acidity and as corbic acid content. The effects of various surface treatments on 'Vietnamese' guava with LDPE shrink and cling wrap packaging, 1%, 5%, 10% and 20% liquid paraffin, 10% and 20% palm oil.0.75% and 1% semperfresh (fatty acid sugarester), and 2% and 3% starch on the storage life at 10˚C were studied. LDPE shrink wrap packaging was most effective in reducing the weight loss and maintaining the hardness of guava. The skin colour of guava was maintained by 20% palmoil until 8 weeks storage. Among the treatments , only cling wrap packaging could maintain the as corbic acid content o f the guava until 8 weeks storage. Twenty percent palm oil surface coating was found to be the mo s t effective treatment for maintaining the quality of fresh guava stored for 8 weeks at 10°C, followed by shrink wrap and cling wrap packaging. Semperfresh was less effective and paraffin was not suitable for guava, as it caused skin lesioning and impart an unfavourable flavour to the fruit. Starch surface coating caused greater deterioration of guava than in control, untreated fruit. At room temperature, the effect sofcysteine HCI and sodium metabisulphite on candied and pickled dried guava were studied. Higher as corbic acid retention and less colour change were observed in candied dried guava than pickled dried guava. 0.024% cysteine HCI was found to be more effective at maintaining the as corbic acid content and colour compared to 1% sodium metabisulphite.